Importance of the water transport sector for Romania's economy. (September 2019) - Nistor, F; Popa, C
Abstract: The importance of the transport sector for the national economy is given by its impact on growth, employment and sustainable development. The transport sector corresponds to the volume of goods exported or imported. According to EU data, transport and storage costs ma y account for up to 15% of the value of a finished product. Competitive maritime transport can provide many benefits for both the national and local economy. Port activity is complementary to maritime transport and involves the development of services related to transport. In Romania, the involvement of the private sector in water transport activities is confirmed by the over 200 active enterprises in 2017. The present paper highlights the place and role of the water transport sector for the national, regional and local economy by considering the importance of Romania on the map of European trade and the EU transport network.